2009
DOI: 10.1002/poc.1603
|View full text |Cite
|
Sign up to set email alerts
|

Premicellar and micelle formation behavior of aqueous anionic surfactants in the presence of triphenylmethane dyes: protonation of dye in ion pair micelles

Abstract: The premicellar and micelle formation behaviors of four cationic triphenylmethane dyes, viz, Pararosaniline (RN), Crystal violet (CV), Ethyl violet (EV), and Malachite green (MG), in aqueous anionic surfactant solutions of sodium dodecyl sulfate (SDS), sodium dodecyl benzene sulfonate (SDBS), and sodium dodecyl sulfonate (SDSN) have been studied by spectral and surface tension measurements. The study was carried out within a pH range where the dyes are stable in their quinoid forms. The dyes have been found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
5
20
0
Order By: Relevance
“…In aqueous SDS micellar solutions, in accordance with the report of Dutta and associates, 51 practically no changes in malachite green absorbance in time were registered. The pK a app value 11.62 ± 0.09 was determined at dye concentration 1.00 × 10 -5 mol L -1 in 0.01 mol L -1 SDS solutions; I = 0.05 mol L -1 (phosphate buffer solution + NaCl), 2 h after preparation of working solutions.…”
Section: Apparent Ionization Constants Of Indicators In Two-phase Syssupporting
confidence: 58%
“…In aqueous SDS micellar solutions, in accordance with the report of Dutta and associates, 51 practically no changes in malachite green absorbance in time were registered. The pK a app value 11.62 ± 0.09 was determined at dye concentration 1.00 × 10 -5 mol L -1 in 0.01 mol L -1 SDS solutions; I = 0.05 mol L -1 (phosphate buffer solution + NaCl), 2 h after preparation of working solutions.…”
Section: Apparent Ionization Constants Of Indicators In Two-phase Syssupporting
confidence: 58%
“…At higher surfactant concentrations (but below the CMC of the pure surfactant), the nonionic ion-pair surfactants are transformed into cationic surfactant on protonation of the dye in the ion pair. In another similar study [23] involving cationic triphenylmethane dyes with a few anionic surfactants in aqueous medium same type of ion pair was reported to be formed. Spectral changes in the presence of surfactants were related to specific interactions or some changes in the microenvironment.…”
Section: Olson-simonson Modelmentioning
confidence: 84%
“…Dye-surfactant interactions are now a days being widely investigated [20,23,24]. Since crystal violet exists as a carbocation it may be expected that there will be interaction between CV + and anionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the interaction to be of 1:1 stoichiometry, the interaction can be represented as follows [26,[33][34][35]:…”
Section: Equilibrium Analysismentioning
confidence: 99%
“…The type of interactions depends mostly on the chemical structure and nature of both of the interacting compounds [31]. Surface tensiometric studies showed that some ionic surfactants exhibit two distinct CMC's in the presence of some oppositely charged dyes where the dye-surfactant ion pairs behave like nonionic surfactants in the submicellar concentration range [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%